Myeloma and MGUS. (May 2021) - Asher, Samir; Streetly, Matthew J.
Abstract: Plasma cell disorders result from a clonal proliferation of bone marrow plasma cells and range from benign monoclonal gammopathy of undetermined significance (MGUS) to malignant myeloma. Serum or urine monoclonal protein is usually detectable. MGUS is asymptomatic but can progress to myeloma or lymphoma. Myeloma is generally a disease of elderly individuals and presents with variable problems including anaemia, bone pain, fractures, spinal cord compression, renal failure, hypercalcaemia, recurrent infections and hyperviscosity. Diagnosis is based on bone marrow examination, and prognosis is influenced by specific acquired genetic abnormalities. Treatment is required after the development of or to reduce the risk of developing myeloma-related organ or tissue impairment (when specific biomarkers are present). Myeloma is incurable, and treatment combines anti-myeloma chemoimmunotherapy with supportive therapies. Younger, medically fit patients are treated with intensive regimens combining chemotherapy with an autologous stem cell transplant, whereas older patients with co-morbidities and poorer performance status are generally offered less intensive treatment. It has a responding–relapsing disease course with eventual development of drug resistance. However, novel therapy options have improved outcomes in myeloma. These include newer proteasome inhibitors such as carfilzomib and ixazomib, and monoclonal antibodies including the anti-CD38 antibody daratumumab.